Práticas corporais alternativas: possibilidades no universo do aluno com deficiencia mental - Zanella, Ângela Kemel (2012)
Inserted into the line of research in Special Education, this work aims at investigating the contribution of Alternative Corporal Practice classes to its learning and development of mentally disabled students. It was characterized by a multicase study of descriptive nature and qualitative approach, which included three students with mental disability, enrolled in regular classes in Elementary School, Municipal School from Santa Maria, RS, from September to December of 2011. The school chosen for this research belongs to the east region of Santa Maria, and the subjects of this research were selected according to the inclusion criteria: Agate, Topaz and Emerald. Two weekly interventions were realized with each student, besides one hour of observation in the classroom, with each subject from the research. The instruments used were: the identification sheet from each student, descriptive opinion made by the researcher in the end of each intervention, field journal which collected information from the observations in the Physical Education classes, talking to the students principal, teachers and parents, and descriptive opinion made by the student s teachers, carried out in the first and the last day of the interventions. The first impressions about the school and the context of the subjects made the researcher worried. How can we change this reality? Would it be possible to realize the study and observe some kind of cognitive and motor improvement? The results were divided into three subtitles: Learning and Development of a Mentally Disabled student from ACPs: elements that facilitate the acquisition of higher psychological functions ; Contributions to Corporal Image and to communicative aspects from the study s subjects ; Acquisition of higher psychological functions of the mentally disabled student: possibilities from the Social-Interaction theory of Levy S. Vygotsky . Although this work has some new topics, with few studies and insights, it is a study that reinforces this new paradigm within the school context, which reveals that is possible to make progress in this field, being one more possibility in the universe of a mentally disabled student. The ACPs can be differential tools to promote inclusion and integration of MD students in the classroom and in the society. The development and learning of these students depends on the deep connection between student and teacher, goals and tasks, language and signs, school and community.